Comparative efficacy and safety of B-TUVP vs. B-TURP for benign prostatic hyperplasia at a tertiary centre in eastern Nepal - Kumar Shah, Amit; Verma, Sumit; Kharel, Shrijan; Pun, Deepak; Dev Baskota, Bashu (Journal of Chitwan Medical College, 2026)
Introduction: Bipolar transurethral resection of the prostate (B-TURP) is an established surgical treatment for benign prostatic hyperplasia (BPH). Bipolar transurethral vaporization (B-TUVP) of the prostate using a button electrode has emerged as an alternative with potential safety advantages. This study compared the efficacy and safety of B-TUVP versus B-TURP in a tertiary centre in eastern Nepal. Methods: A retrospective cohort study of BPH treated between Jan 2021 and Dec 2024 at B and C Medical College and Teaching Hospital, Birtamod, Nepal, was conducted. Ethical approval was obtained. Patients were categorized into B-TUVP and B-TURP groups. Variables included operative time, irrigation time, haemoglobin drop, hospital stay, catheterization duration, IPSS, Qmax, QOL, and PVRV. Follow-up was at 4, 8, 12, and 24 months. Data analysis was done by SPSS version 29. A p≤0.05 was considered significant. Results: A total of 400 patients (B-TUVP n=200, B-TURP n=200) were included. Baseline characteristics were comparable between groups. B-TUVP had longer operative time (60.94±18.64 vs 49.85±9.35 min, p=0.001) but shorter postoperative irrigation time (11.03±0.82 vs 14.99±2.02 h, p=0.001), less haemoglobin drop (0.74±0.14 vs 0.99±0.11 g/dL, p=0.001), shorter hospital stay (2.93±0.83 vs 3.50±1.10 days, p=0.001) and catheterization duration (3.03±0.84 vs 3.99±1.35 days, p=0.001). IPSS and Qmax improved significantly in both groups, with B-TURP showing better early outcomes. Long-term outcomes at 24 months were comparable in QOL, PVRV, and complication rates. Conclusions: B-TUVP is a safe and effective alternative to B-TURP for surgical management of benign prostatic hyperplasia, offering favourable perioperative outcomes with comparable long-term efficacy.